FORMATIVE ASSESSMENT IN A POSTGRADUATE TRAINING PROGRAM– DOES THE MODEL WORK? - Sarkar, Sonali; C, Premarajan K; Roy, Gautam; Kumar, Ganesh; Kar, Sitanshu Sekhar; Sahoo, Swaroop Kumar; Lakshminarayanan, Subitha (Indian Journal of Community Health, 2013)
Background: Lack of assessment and feedback based on observation is one of the most serious deficiencies in the current medical education practice. Formative assessment strategies in postgraduate education can be affective when they are integral to the learning process. Seminars and journal club presentations are integral to the postgraduate education in all medical institutions. Methods: This study was done to assess a structured tool for evaluation of seminars and journal clubs by postgraduates in Community Medicine (as part of formative assessment) based on rater reliability and efficacy of feedback. Results: The scale having five domains namely justification for the topic or the journal article, presentation skills, slide preparation, slide content and discussion, had high inter-rater reliability with intra class coefficient of 0.861 (95% CI 0.632 to 0.958), ‘p’ of 0.000. There was a significant improvement of the students over three journal club presentations in four out of five domains.Conclusions: This study has shown that use of rating scales during seminar and journal club presentations, when combined with feedback, can be an effective tool in formative assessment thereby supporting and enhancing the learning process.